Representasi Keberanian dan Kebebasan Perempuan dalam Sampul Singel Non-album ‘Pelangi Cinta’ Karya Diskoria bersama Afifah Yusuf - Satiya, Firli Daffa; Maheswara, Adhitya M (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2024)
The album cover of a song has an important role in attracting public interest in the song and also becomes an intermediary medium in conveying messages from musicians to their fans. The focus of this research is the interpretation of the cover of the single 'Pelangi Cinta' by Diskoria with Afifah Yusuf, which seems controversial if interpreted simply. The results of this research show that a music cover, in fact, can represent the intention or message that the musician wants to convey. The cover of Diskoria's non-album single with Afifah Yusuf is successful in conveying a strong feminine message without discrediting women. This research method uses descriptive qualitative method and uses Roland Barthes' semiotic theory. The purpose of this research is to describe the relationship between signs and meanings of women's courage in expressing their sexuality through the visual design of the cover of Diskoria's non-album single with Afifah Yusuf. Keywords: Pelangi Cinta, Diskoria, Album Cover, Semiotic, Sensuality